Firm Performance and Corporate Social Responsibility: Spatial Context and Effect Mechanism - Jiafeng Gu (SAGE Open, 2023)
This study investigates the effect of firm performance on corporate social responsibility (CSR) in a specific spatial context. The results for a sample of 1,557 listed companies in China suggest that a firm’s CSR performance level is influenced by that of nearby firms. This study also confirms the indirect link between financial and CSR performance through the mediating role of institutional and executive shareholding rates. In addition, the empirical evidence in this study not only supports the spatial context-sensitive thesis but, more importantly, proposes a spatiotemporal context-sensitive thesis. It provides strong empirical support for the true relative value of the spatiotemporal context affecting CSR performance, which yields important theoretical, methodological, and policy implications.